KARAKTERISTIK TAFSIR NUSANTARA (Studi Metodologis atas Kitab Turjumun al-Mustafid Karya Syekh Abdurrauf al-Singkili) - Abdullah, Rukiah; Masduki, Mahfudz (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
"> This work tries to scrutinize an interpretation methodology on opus inNusantara (Archipelago) written by Abdurrauf al-Singkili, Tafsir Turjumunal-Mustafid. This research is a library research uses descriptive-analyticaland with historical–critical approach. I conclude that: (a) interpretationmethod that were used by Abdurrauf al-Singkili is an inter-text method; (b)refer to the exegete of surah Yasin, this work has a linguistic nuance; and (c)the approach which is used by Abdurrauf al-Singkili is textual approach,the practice of the interpretation is text-oriented.